A Modular Approach to the Total Synthesis of Tunicamycins1. Issue 22 (14th April 2015) - Li, Jiakun; Yu, Biao
Abstract The tunicamycins constitute a delicate mimic of the bisubstrate intermediates of N‐acetyl‐D‐hexosamine‐1‐phosphate translocases and thus inhibit bacterial cell‐wall synthesis and the N glycosylation of eukaryotic proteins. An efficient approach to the synthesis of this unique type of nucleoside antibiotics is now reported and features the assembly of five modules in a highly stereoselective and robust manner. A Mukaiyama aldol reaction, intramolecular acetal formation, gold(I)‐catalyzed O and N glycosylation, and final N acylation were used as the key steps.